Varve record reveals rapid development of hypolimnetic anoxia in a Northern European lake resulting from urban activities - Billah, Mohib; Tuovinen, Nanna; Salminen, Sarianna; Tylmann, Wojciech; Kalliokoski, Maarit; Saarni, Saija (Elsevier BV, 2026)
Human activities can significantly impact the environmental conditions of water bodies adjacent to urban areas. Maljalahti Bay, situated near the city of Kuopio at the northern end of Lake Kallavesi, has experienced numerous substantial, well-documented urban changes over the past centuries. We investigated the lake response to the influence of anthropogenic activities at Maljalahti through analysis of diatom assemblages and physical and geochemical properties of the Maljalahti sediment record. The sediment core was dated using varve counts and the vertical distribution of 137Cs and 210Pb. The 100-cm-long sediment record contains 95 varves, and an 8-cm-thick clastic sequence at 100–92 cm sediment depth, likely corresponding to the partial filling of the bay that started in 1913. This event, along with the initiation of sewage discharge into the bay in 1907, likely contributed to eutrophication and declining water-column oxygen conditions and the deposition of sediment with weak varve structure since the 1920s. More prominent varves appear in the sediment record since the 1980s, after the construction of a breakwater in 1978. The good preservation of these varves suggests either rapid sedimentation or the occurrence of oxygen-poor conditions. The diatom assemblage data imply that gradual eutrophication commenced when wastewater was directed to the Bay, and the construction of the wastewater treatment plant in 1974 resulted in a lower nutrient load on the Bay. Maljalahti Bay system experiences seasonal anoxia after 20 years of sewage loading, emphasizing the need for effective water exchange despite preventive measures failing to improve water quality.